Neurobrucellosis: a case report - Patil, Supriya; Narkhede, Meenakshi G. (International Journal of Research in Medical Sciences, 2017)
Neurologic involvement of brucellosis is common but exact prevalence of it is unknown due to difficulty in diagnosis and inadequate reporting all over the world. Neurologic involvement may manifest as chronic meningitis, lymphocytic meningoencephalitis, a variety of cranial nerve deficits, or ruptured mycotic aneurysms. We report a case of young male who had history of fever and headache on and off for 2 years and later developed signs of meningitis, lateral rectus palsy, altered sensorium and bilateral papilledema. He did not respond to anti-tubercular therapy and antibiotics. CT scan and MRI brain were normal. He had hepato-splenomegaly with small hypoechoic lesions in the spleen. CSF culture grew gram negative bacilli. Brucella IgG antibodies in serum by EIA 7, IgM negative, Brucella antigen titer was positive, 1:160. Patient received inj. streptomycin 0.75 g for 21 days and doxycycline 100 mg twice daily doxycycline for 6 weeks. The complete improvement in patient’s condition after a long lasting illness motivated authors to report this case. Delay or failure in diagnosis of this treatable disease may lead to significant morbidity and mortality so high index of suspicion should be kept in such cases.